2017
DOI: 10.17650/1726-9784-2017-16-2-82-90
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic identification of hnRNP family members and other proteins involved in splicing in human cultured cells

Abstract: Introduction. Heterogeneous nuclear ribonucleoprotein A1 (hnRNP А1) and other RNA-binding proteins involved in splicing participate in realization of genetic information and can be greatly changed in pathological conditions including tumors. Objective. Proteomic study of hnRNP A1 and other RNA-binding splicing proteins in 10 human malignant and non-malignant cultured cell lines of mesenchymal and epithelial origin. Materials and methods. Two-dimensional gel electrophoresis of adenocarcinomas (LNCaP, DU-145, PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In addition, in a comparative proteomic study, it was shown that the content of hnRNP-A1 in cancer cells is usually higher than in adjacent normal tissues [68]. In our laboratory, a proteomic analysis of ten cultured HMC lines revealed hnRNP-A1 as one of the 500 most abundant proteins [69].…”
Section: General Properties Of Several Main Human Hnrnps Involved mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, in a comparative proteomic study, it was shown that the content of hnRNP-A1 in cancer cells is usually higher than in adjacent normal tissues [68]. In our laboratory, a proteomic analysis of ten cultured HMC lines revealed hnRNP-A1 as one of the 500 most abundant proteins [69].…”
Section: General Properties Of Several Main Human Hnrnps Involved mentioning
confidence: 99%
“…Information on the third transcript of the HNRNPA1 gene is extremely limited (P09651-3 UniProt). Nonetheless, recently, in our laboratory, trace amounts of the corresponding protein product in human mesenchymal stem cells (SC5-MSC) were detected by proteomic analysis [69].…”
Section: General Properties Of Several Main Human Hnrnps Involved mentioning
confidence: 99%
See 1 more Smart Citation